2015
DOI: 10.1038/npjschz.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

The impact of premorbid and current intellect in schizophrenia: cognitive, symptom, and functional outcomes

Abstract: Background:Cognitive heterogeneity among people with schizophrenia has been defined on the basis of premorbid and current intelligence quotient (IQ) estimates. In a relatively large, community cohort, we aimed to independently replicate and extend cognitive subtyping work by determining the extent of symptom severity and functional deficits in each group.Methods:A total of 635 healthy controls and 534 patients with a diagnosis of schizophrenia or schizoaffective disorder were recruited through the Australian S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 45 publications
7
62
3
4
Order By: Relevance
“…The preserved group is defined by a premorbid IQ score > 90 and < 10 points of decline from premorbid to current IQ, the deteriorated group has ≥ 10 IQ points decline, and the compromised group has a premorbid IQ < 90 (and a IQ decline < 10 points) (Weickert et al, 2000). Studies using this clinical classification method have confirmed the groups using empirical clustering methods (Weickert et al, 2000;Wells et al, 2015). The subgroups have been shown to differ in cognitive profile (Weickert et al, 2000;Wells et al, 2015), functional outcome (Wells et al, 2015), symptom profile (Wells et al, 2015), and brain volume or cortical thickness (Weinberg et al, 2016;Van Rheenen et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…The preserved group is defined by a premorbid IQ score > 90 and < 10 points of decline from premorbid to current IQ, the deteriorated group has ≥ 10 IQ points decline, and the compromised group has a premorbid IQ < 90 (and a IQ decline < 10 points) (Weickert et al, 2000). Studies using this clinical classification method have confirmed the groups using empirical clustering methods (Weickert et al, 2000;Wells et al, 2015). The subgroups have been shown to differ in cognitive profile (Weickert et al, 2000;Wells et al, 2015), functional outcome (Wells et al, 2015), symptom profile (Wells et al, 2015), and brain volume or cortical thickness (Weinberg et al, 2016;Van Rheenen et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…These findings were recently replicated in a large independent sample of 534 chronically ill patients with schizophrenia and 635 healthy controls. 4 These IQbased subgroups were also identified in similar proportions of individuals with first-episode psychosis. 5,6 Despite the identification of unique, intellectually based subgroups, the nature and extent of cognitive deficits in these subgroups remain somewhat unclear because investigators 3,[7][8][9][10] have found that even those with putatively preserved IQ perform significantly worse than matched healthy individuals on a range of cognitive abilities.…”
mentioning
confidence: 91%
“…Through identifying distinct clusters of participants who share a homogenous cognitive profile, several subgroups that characterise the within-group cognitive variability prevalent among people with psychosis have been consistently identified. Broadly, two anchoring cognitive profiles repeatedly emerge, a severely impaired subgroup and a cognitively intact subgroup, with a varying number of intermediate profiles of mixed/specific cognitive deficits emerging in-between (Burdick et al, 2014;Lewandowski et al, 2018;Van Rheenen et al, 2017;Weickert et al, 2000;Wells et al, 2015). These subgroups can be identified at first episode (Reser et al, 2015;Uren et al, 2017), transcend the familial and psychosis spectrum (Burdick et al, 2014;Hoti et al, 2004;Lewandowski et al, 2014;Van Rheenen et al, 2017), exhibit distinctive brain structure (Czepielewski et al, 2017;Van Rheenen et al, 2018;Woodward & Heckers, 2015), and display altered response to treatment and functional outcomes (Gilbert et al, 2014;Uren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%